Archetypical symbols as the determinants of poetic model of the world - Лисенко, Наталя Олександрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article considers the determinants of poetic model of the world; in particular, the archetipic model of world, some features  of which are reserved by consciousness and  subconsciousness of  any person including the poet  as well as the differentiation of notions of model of the world and images of the world, individual poetic model of the world and works out in detail the definitions of these terms. The article proves that the formation of image of the world  precedes  the arising  of the model of the world and individual poetic model is the logic consequence of creative and poetic mastering of the reality.